ANALGESIC ACTIVITY TEST OF WARU (Hibiscus tiliaceus L.) LEAVES ETHANOL EXTRACT IN MALE WHITE MISCULES (Mus musculus) - Situmorang, Novidawati Boru; Widya Ningsih, Silvia (Jurnal FARMASIMED (JFM), 2022)
Herbal remedies in therapy have been used in the treatment of pain since time immemorial. Pain is a sensory and emotional event that causes discomfort due to tissue damage. Most of the analgesics used in modern medicine have side effects on either the gastro-intestinal tract or the nervous system. Empirically waru leaves have been used as traditional medicine. The purpose of this study was to evaluate the analgesic effect of the ethanol extract of waru leaf and compare it with mefenamic acid tablets and then measured by the plantar test infra red (IR) 96 nm. Twenty five mice were divided into five groups. Three of them were treated with ethanol extract of waru leaves with doses of 100, 200, 300 mg/kgbw, 0.5% Na-CMC (negative control), and 500 mg Mefenamic Acid tablets (positive control). Infrared pain induction was performed every 10 minutes for 60 minutes. The maximum analgesic activity was indicated by a dose of 300 mg/kg body weight extract at 60 minutes which was 23.8 where the effectiveness was almost the same as the standard drug Mefenamic Acid, which was 24.3 while the dose of 200 mg/kgBB was 20.9 and 100 mg/kgBW was 19.9. The data obtained were then processed using one way ANOVA. The conclusion of the study revealed that hibiscus leaf (Hibiscus tiliaceus L.) has significant analgesic properties, especially in higher doses